2016
DOI: 10.1111/j.1936-704x.2016.03231.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Environmental Tracers in the Memphis Aquifer and Implication for Sustainability of Groundwater Resources in the Memphis Metropolitan Area, Tennessee

Abstract: Fourteen years of results from environmental tracer sampling for 3H, He isotopes, noble gases, and SF6 in production wells screened in the Memphis aquifer in Memphis, Tennessee, are presented and used to determine the age and mass proportion of modern water (<60 years old) pumped from this regionally important public supply aquifer. The results indicate persistent presence of modern water in water pumped from one or more production wells in most of the well fields sampled. The percentage of modern water is qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…Traditionally, the public water supply authority in the Memphis area assumed that the UCCU could fully protect the water in the Memphis aquifer from downward leakage of the contaminated or poor-quality groundwater from the overlying Shallow aquifer. However, recent studies show that at some locations, the UCCU is thin or absent, which leads to the contribution of water from the Shallow aquifer to the Memphis aquifer [9][10][11]14]. Hence, sustainable water management in the Memphis area requires the locations of breaches in the UCCU to ensure the protection of water pumped from the production wells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the public water supply authority in the Memphis area assumed that the UCCU could fully protect the water in the Memphis aquifer from downward leakage of the contaminated or poor-quality groundwater from the overlying Shallow aquifer. However, recent studies show that at some locations, the UCCU is thin or absent, which leads to the contribution of water from the Shallow aquifer to the Memphis aquifer [9][10][11]14]. Hence, sustainable water management in the Memphis area requires the locations of breaches in the UCCU to ensure the protection of water pumped from the production wells.…”
Section: Discussionmentioning
confidence: 99%
“…So far, two different approaches have been employed to answer this question. The first approach is the "geochemical investigation" [7][8][9][10][11][12][13] where groundwater samples are analyzed to identify geochemical signatures that are attributed to surface water within the groundwater. Within the Memphis area, age-dating of groundwater by using tritium-helium-3 and sulfur hexafluoride support geochemical data, and reflects the influence of modern water (<50 years) in the Memphis aquifer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, two different approaches are employed to answer this question. The first approach is the "geochemical investigation" (Neretnieks, 1981;Busenberg et al, 1993;Larsen et al, 2003Larsen et al, , 2013Larsen et al, , 2016Ivey et al, 2008;Majidzadeh et al, 2017) where groundwater samples are analyzed to identify geochemical signatures attributed to surface water within the Memphis aquifer water. Within the Memphis area, age-dating of groundwater using tritium-helium-3 and sulfur hexafluoride support 6 geochemical data and reflects the influence of modern water (< 50 years) in the Memphis aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that modern water contributes up to 40% of groundwater withdrawn from production wells -in one case production water contains as much as 75% modern water (Larsen et al, 2003(Larsen et al, , 2013(Larsen et al, , 2016. The second approach is the "geological investigation" in which techniques such as surveying stratigraphic thickness and water table elevation, electrical resistivity surveys, shear-wave seismic reflection, and other geophysical analyses are used to identify gaps in impermeable layers (Parks, 1990;Sutinen, 1992;Besson et al, 2004;Waldron et al, 2009;Schoefernacker, 2018).…”
Section: Introductionmentioning
confidence: 99%